Description on cognitive level of mid and final test for 7th grade in Makassar - Nurul Asmi; Ruslan; Fajar Arwadi (ARRUS Journal of Mathematics and Applied Science, 2021)
This research is a descriptive research with qualitative approach. The purpose of this research is to describe the cognitive level of UTS and UAS made by teacher Mathematics class VII. The subject is midterm exam and final exam class VII created by the mathematics teacher according to curriculum 2013. This Data analyze based on three levels of cognitive, namely (1) Level 1 knowing in the form of cognitive processes, remembering and understanding, (2) Level 2 applying in the form of cognitive processes, cognitive processes applying, and (3) Level 3 reasoning cognitive processes analyzing, evaluating and creating. Generally cognitive levels distributed in a comprehensive way so that educational evaluations measure educational attainment. The data also obtained using classification paper of level cognitive, interview guidelines and expert validator. The results showed that subjects are dominated by the level of knowing with a percentage of 50% by 10 items in the cognitive processes of understanding. While the level of application with a percentage of 45% is 9 items in the cognitive process of applying and the level of reasoning with a percentage of 5% is 1 item of the cognitive process analyzing.